2020
DOI: 10.3390/ijms21041336
|View full text |Cite
|
Sign up to set email alerts
|

Direct Interaction between Calmodulin and the Grb7 RA-PH Domain

Abstract: Grb7 is a signalling adapter protein that engages activated receptor tyrosine kinases at cellular membranes to effect downstream pathways of cell migration, proliferation and survival. Grb7’s cellular location was shown to be regulated by the small calcium binding protein calmodulin (CaM). While evidence for a Grb7/CaM interaction is compelling, a direct interaction between CaM and purified Grb7 has not been demonstrated and quantitated. In this study we sought to determine this, and prepared pure full-length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…Itk (interleukin-2-inducible tyrosine kinase) belongs to the Tec kinase family ( 84 ). Also, a more recent study that aimed to investigate the direct interaction between CaM and the growth receptor bond 7 (Grb7) protein showed that CaM interacts with the PHD of Grb7 ( 85 ). There, CaM’s peculiar binding motif was mapped to the β -sheet and not an α -helical region ( 85 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Itk (interleukin-2-inducible tyrosine kinase) belongs to the Tec kinase family ( 84 ). Also, a more recent study that aimed to investigate the direct interaction between CaM and the growth receptor bond 7 (Grb7) protein showed that CaM interacts with the PHD of Grb7 ( 85 ). There, CaM’s peculiar binding motif was mapped to the β -sheet and not an α -helical region ( 85 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, a more recent study that aimed to investigate the direct interaction between CaM and the growth receptor bond 7 (Grb7) protein showed that CaM interacts with the PHD of Grb7 ( 85 ). There, CaM’s peculiar binding motif was mapped to the β -sheet and not an α -helical region ( 85 ). The NMR CSP data for the Akt PHD indicated that it interacts with CaM via the β 1- β 2 and β 6- β 7 loops ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…26 La región central de GRB7 tiene un dominio de cerca de 300 aminoácidos que muestran una alta homología con un gen de Caenorhabditis elegans, el gen Mig-10. 27 Este ha sido involucrado en la migración de células neuronales durante el desarrollo, por lo cual se ha sugerido un rol de GRB7 en la regulación de la migración de células mamíferas. 28 La región central contiene tres dominios: RA (asociado a Ras) por lo cual se cree que GRB7 interactúa con las GTPAsas de la superfamilia Ras y de esta forma regula la progresión del cáncer, un dominio de homología a pleckstrina (PH) y el dominio BPS (entre PH y SH2) el cual interactúa principalmente con el receptor de insulina activado en el dominio SH2.…”
Section: G R B 7 E S T Ru C T U R a Y U B I Cac I ó Nunclassified
“…The Ca 2+ -bound C-lobe and Ca 2+ -free N-lobe bind distinct sites, which leads to stabilization of the adenylyl cyclase catalytic site [26] (Figure 1). CaM interacts with the Ras-association (RA) and pleckstrin homology (PH) domains of the adaptor protein growth factor receptor-bound protein 7 (Grb7) in a calcium-dependent manner and regulates its subcellular localization [27,28]. It was proposed that CaM binding may open the Grb7 structure, facilitating the RA and PH domains to interact with activated RAS and the membrane, respectively.…”
Section: Mechanisms By Which Ca 2+ -Cam Regulates Target Proteinsmentioning
confidence: 99%